2009
DOI: 10.1103/physrevlett.103.097201
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Antiferromagnetic Order in FeO Nanolayers

Abstract: We have studied the evolution of the magnetic state of a nanometer thick antiferromagnetic (AFM) FeO layer during its formation using nuclear resonant scattering of synchrotron radiation. In contact to ferromagnetic Fe, the FeO layer does not show magnetic order at room temperature (RT). Once embedded between two Fe layers, magnetic coupling to the adjacent ferromagnets leads to a drastic increase of the Néel temperature far above RT, while the blocking temperature remains below 30 K. The presented results evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
3
23
1
Order By: Relevance
“…Note that for bulk FeO the Néel temperature (T N ) is 198 K, but it has been shown that thin FeO layers with Fe on either side show T N well above room temperature due to exchange interactions with FM spins. 60 Given the large fractional decrease in ferromagnetic components, it is unexpected that the saturation magnetization did not decrease more, since FeO fraction is 64 wt%. It may be that Fe/FeO interfaces are ferrimagnetic, resulting in more saturation than would be expected given a mixture of the pure phases.…”
Section: Results and Discussion A Structural Characterizationmentioning
confidence: 98%
“…Note that for bulk FeO the Néel temperature (T N ) is 198 K, but it has been shown that thin FeO layers with Fe on either side show T N well above room temperature due to exchange interactions with FM spins. 60 Given the large fractional decrease in ferromagnetic components, it is unexpected that the saturation magnetization did not decrease more, since FeO fraction is 64 wt%. It may be that Fe/FeO interfaces are ferrimagnetic, resulting in more saturation than would be expected given a mixture of the pure phases.…”
Section: Results and Discussion A Structural Characterizationmentioning
confidence: 98%
“…The authors attributed this to the formation (unwanted) of an Fe-O reaction product at the interface introducing an AFM spin coupling. In our sample, the possible formation of Fe-related AFM oxides such as Fe-O [30], c-Fe 2 O 3 [31] and Fe 3 O 4 [32] at the Py/MgO interface cannot be entirely ruled out. But, the T b 's associated with these oxides have been found to be $30 K, 100 K and 120 K, respectively, well below the observed T b > 400 K in our work.…”
Section: Introductionmentioning
confidence: 87%
“…The origin for this coupling is the reduction of the multi-valent (2 + , 3 + ) native Fe-oxide to single valent (2 + ) FeO upon coverage with metallic Fe [33]. The ultrathin buried FeO layers exhibit an enhanced Neel temperature well above room temperature [34]. The exchange coupling between the Fe layers and the laterally inhomogeneous (rough) FeO layers leads to a spin frustration that results in canted moments rather than parallel or antiparallel moments between adjacent Fe layers [24].…”
Section: Non-collinear Coupling In Fe/fe-oxide Multilayersmentioning
confidence: 99%